Cambridge academic English - Thaine, Craig (Cambridge University Press, 2012)
A three-level (B1+ to C1) integrated skills course for higher education students at university or on foundation courses. The B1+ Intermediate Student's Book introduces students to the characteristics of written and spoken academic texts. Students are guided towards developing relevant strategies for setting study goals and approaching these texts. From asking for help, understanding essay questions to planning essay paragraphs and listening for gist and detail, students have a wealth of opportunities to practice all core academic skills. The course develops independent learning skills and critical thinking through 'Study Tips' sections and allows for personalisation of learning in the 'Focus on your subject' sections. Five lecture skills units provide authentic practice in listening to lectures and note-taking